THE EFFECT OF USING THE MARKET PLACE ACTIVITY METHOD ON STUDENT ACHIEVEMENT IN FIQH SUBJECTS - Mashuri, Imam; Ramadhani, Lutfia (INCARE, International Journal of Educational Resources, 2023)
This study explains the influence of the Market Place Activity Method learning method on the learning achievement of grade X students who have been at NU Genteng High School. This research is an experimental quantitative type research. The sample in this study was 60 students who were members of class X IPS 1 and X IPS 2. Data were retrieved using multiple choice tests. For data analysis using the Independent Sample T-Test, Tast. The results of this study show the influence of the Market Place Activity method on learning achievement with the help of SPSS software version 16 shows the calculated t value is higher than the table t value. The results of the t test showed that the calculated t value of post-learning student learning outcomes with the Place Activity Mockup method was 7,571 (7,571>2,086), then from this study it can also be concluded that the value of student learning achievement influenced by the Market Place Activity method is higher than the learning achievement of control class students. The average score of student learning achievement or the mean of the experimental class was 84,500 and the average score or mean of the control class was 70,667, the difference in the average or mean score of 13,833 (84,500-70,667=13,833). From this study, it can be concluded that the use of the Market Place Activity method affects the value of student achievement. Thus it is concluded that in this study the alternative hypothesis (Ha) is accepted while the null hypothesis (H0) is rejected.